MAXIMAL VOWEL SPACE METOD IN ANALYSIS OF VOWELS IN PRELINGUAL SPEECH PHASE - Vojnović, Milan; Bogavac, Ivana; Jeličić Dobrijević, Ljiljana (Specijalna edukacija i rehabilitacija, 2014)
The main problems in analysis of vowels which occur in prelingual speech phase are centralization of utterance and unknown dimension of vocal tract. Most researches in this field are based on analysis of maximal vowel space (MVS) because the discrimination of vowels is very difficult in this early period. MVS analysis includes the estimation of vocal tract (VT) physical dimensions. Research aim was to estimate and define changes in the vowel pronunciation during prelingual speech phase. The analysis and voice recording was performed in a two month old child till he was one year old. Recording had been done in 42 sessions, 4 sessions every month in average. Sound segments that look like vowel pronunciation were extracted from the recordings and were used for the formant frequencies estimation by PRAAT software. The Burg method was used for formant frequency estimation. Research results showed that MVS can be used in diagnostic procedure from child’s earliest age. MVS analysis is appropriate to child’s earliest age as it demands that child pronounces individual phonemes, and not to answer on speech stimuli. This results need to be confirmed on larger sample when extended analysis should define criteria for discrimination typical and atypical formant frequencies spaces.